Meningitis secondary to rectothecal fistula associated with congenital anterior meningocele - Kaitlin Larson; Juan Pablo Gurria; Jennifer S. Ronecker; Rachael Stottlemyre; David M. Notrica (Elsevier, 2022)
Introduction: Meningitis secondary to rectothecal fistula is an exceptionally rare phenomena which has previously been reported exclusively in the setting of Currarino Syndrome for the pediatric population. Case presentation: We describe the case of a neonate presenting with polymicrobial meningitis due to rectothecal communication via congenital anterior sacral meningocele in the absence of an anorectal malformation. The authors opted for expeditious surgical resection of the fistulous tract and closure of the thecal sac using a posterior sagittal approach to the presacral space. The patient completed a course of intravenous antibiotics postoperatively. Discussion: This case highlights the first reported neonatal case of rectothecal fistula in the absence of an anorectal anomaly. The surgical approach is described.